Análisis de las herramientas para la gestión de incidencias de los clientes de la empresa Controlnet de la ciudad de Vinces. - Vera Yépez, Noe Alexander (2023)
The objective of this case study called Analysis of the tools for the management of customer incidents of the Controlnet company in the city of Vinces, was to improve the management of customer incidents by analyzing tools that help the company to improve customer satisfaction. An incident tool is a system that facilitates the administration of reported incidents and helps provide better customer service. Controlnet, a company dedicated to the installation of Internet service, uses instant messaging applications to manage and communicate its incidents to technical support technicians so that they can solve the incident. The company's incident process was examined and some shortcomings were assessed, such as the lack of prioritization of the type of incident. Exploratory and descriptive research was used for the case study. We proceeded to explore three tools in the market that are used for the management of incidents of the companies and described the process that the company performs to manage the incidents with their respective shortcomings that make the customer satisfaction decreases. Surveys directed to the company's employees were used to collect data to support the research, such as the types of disadvantages of the tools they use or whether it is positive to improve customer service with other tools. In general, the case study focuses on the fact that customer service should be paramount in any company, using tools that are suitable to better manage the incidence and increase customer satisfaction.